Climate and topographic controls on simulated pasture production in a semiarid Mediterranean watershed with scattered tree cover - Lozano-Parra, J; Maneta, M P; Schnabel, S (HYDROLOGY AND EARTH SYSTEM SCIENCES, 2014)
Natural grasses in semiarid rangelands constitute an effective protection against soil erosion and degradation, are a source of natural food for livestock and play a critical role in the hydrologic cycle by contributing to the uptake and transpiration of water. However, natural pastures are threatened by land abandonment and the consequent encroachment of shrubs and trees as well as by changing climatic conditions. In spite of their ecological and economic importance, the spatiotemporal variations of pasture production at the decadal-century scales over whole watersheds are poorly known. We used a physically based, spatially distributed ecohydrologic model applied to a 99.5 ha semiarid watershed in western Spain to investigate the sensitivity of pasture production to climate variability. The ecohydrologic model was run using a 300-year-long synthetic daily climate data set generated using a stochastic weather generator. The data set reproduced the range of climatic variations observed under the current climate. Results indicated that variation of pasture production largely depended on factors that also determined the availability of soil moisture such as the temporal distribution of precipitation, topography, and tree canopy cover. The latter is negatively related with production, reflecting the importance of rainfall and light interception, as well as water consumption by trees. Valley bottoms and flat areas in the lower parts of the catchment are characterized by higher pasture production but more interannual variability. A quantitative assessment of the quality of the simulations showed that ecohydrologic models are a valuable tool to investigate long-term (century scale) water and energy fluxes, as well as vegetation dynamics, in semiarid rangelands.
APS
Keywords: degradation; ecohydrology; Grasslands; pasture production; semiarid rangelands; soil erosion

A model-based integrated assessment of land degradation by water erosion in a valuable Spanish rangeland - Ibáñez, J; Contador, J F Lavado; Schnabel, S; Fernández, M Pulido; Valderrama, J Martínez (Environmental Modelling & Software, 2014)
This paper presents an integrated assessment model aimed at evaluating land degradation by water erosion in dehesa rangelands in the Iberian Peninsula. The model is built following the system dynamics approach. The degradation risk is likened to the probability of losing a certain amount of soil within a number of years, as estimated over a great number of stochastic simulations. Complementary indicators are the average times needed to lose different amounts of soil over the simulations. A group of exogenous factors are ranked in order of importance. These factors are mainly climatic and economic and potentially affect soil erosion. Calibration is carried out for a typical dehesa defined over 22 working units selected from 10 representative farms distributed throughout the Spanish region of Extremadura. The degradation risk turns out to be moderate. The importance of climatic factors on soil erosion considerably exceeds that of those linked to human activities.
Keywords: Dehesa rangeland; Integrated assessment model; Land degradation; soil erosion; System dynamics

The role of interannual rainfall variability on runoff generation in a small dry sub-humid watershed with disperse tree cover - Schnabel, S; Gomez GUTIÉRREZ, A (Cuadernos de Investigación Geográfica, 2013)
Recent studies in small experimental catchments under Mediterranean-type climate revealed a complex hydrological catchment response, presenting saturation excess runoff generation and, to a minor degree, infiltration excess flow. Many of these catchments, however, belong to areas with sub-humid or humid Mediterranean climate. Catchment studies were carried out since 1991 in savannah-like grazed land (dehesas), which are widespread in south-western Spain, and also elsewhere in the Mediterranean. Albeit knowledge gained by previous studies, no thorough analysis has been carried out on the temporal variation of discharge production using the complete dataset. The objectives include i) an analysis of the temporal variation of discharge and rainfall at different temporal scales, ii) exploration of the role of antecedent soil moisture conditions in runoff production, iii) empirical modeling of rainfall- runoff relationships at the event scale and iv) definition of the importance of interannual rainfall variation on discharge production. The analysis were based on rainfall and runoff which were monitored at a time resolution of 5 minutes and periodically measured soil moisture from various depth in the valley bottom. Regression analysis as well as the comparison of hydrographs illustrate on the importance of antecedent rainfall conditions. Soil moisture in the valley bottom was crucial to understand the hydrological behaviour of the catchment. A soil moisture threshold of 0.37 m3 m-3 was defined above which runoff coefficients increase sharply. This situation is reached with 170 mm of antecedent rain falling in a continuous way. The results indicate that saturation excess flow and preferential subsurface flow processes are responsible of most of the runoff generated. Hortonian type overland flow dominates under dry soil conditions and is produced by high intensity rainfall. Non-linear regression analysis with data grouped according to antecedent catchment conditions produced highly significant regression models, explaining event discharge with three variables: Maximum 60-minute rainfall intensity (I60), event rainfall minus I60 and mean antecedent daily rainfall. Variability of monthly runoff is best explained by interannual rainfall variation rather than by mean seasonal distribution. During droughts, which are a common feature in the Mediterranean, discharge was very low. Runoff is highly concentrated in time with 10% of the months accounting for 85% of total discharge.
Keywords: Dehesa; discharge; Drought; empirical modelling; RAINFALL; Soil moisture

Soil water repellency in rangelands of Extremadura (Spain) and its relationship with land management - Schnabel, S; Pulido-Fernández, M; Lavado-Contador, J F (Catena, 2011)
Soil water repellency reduces inﬁltration capacity, enhancing overland ﬂow and even runoff production, and may produce patchiness in water inﬁltration at the hillslope scale. Knowledge about hydrophobicity in rangelands of Mediterranean type climate and its relation with vegetation cover and land management is sparse. The objectives of the present work are to determine the degree and spatial occurrence of soil water repellency and to deﬁne its relationship with site characteristics, such as soil, vegetation and land management in rangelands of SW Spain. Field work was conducted in September 2009 in 22 environmental units belonging to 10 farms, distributed throughout the region of Extremadura. The Molarity of an Ethanol Droplet (MED) method was used for measuring water repellency of the soil surface. A total of 725 points were sampled and the study was combined with a detailed vegetation survey, the determination of soil properties and of land use and management characteristics. More than 70% of the measurement points were hydrophilic, however differences between farm units were found. The highest values of hydrophobicity were observed on soil surfaces below the canopy of holm oaks, as compared to the low values found below shrub canopies (Retama sphaerocarpa) and in open areas. With respect to ground cover, water repellency was highest at sites covered by holm oak litter. At soil surfaces covered by cork oak litter, dry grass and mosses the degree of repellency was lower. Almost all sites with a bare soil surface were hydrophilic, independent of whether these were located below a tree canopy or in open areas. A signiﬁcant positive relationship between livestock density and the degree of bare soil existed, and consequently, areas with high animal numbers were dominantly hydrophilic. No signiﬁcant relationships were encountered between the degree of soil water repellency and soil properties.
Keywords: Mediterranean type climate; Rangelands; Soil surface cover; water repellency

DINÁMICA DEL AGUA DEL SUELO EN DEHESA BAJO DIFERENTES CUBIERTAS VEGETALES. RESULTADOS PRELIMINARES. - Lozano Parra, F J; Schnabel, S; Ceballos Barbancho, A (Estudios en la Zona no Saturada del Suelo, 2008)
Dehesa ecosystems, characterized by a disperse tree cover of the genus Quercus, constitute a resource of great importance in large parts of SW Iberian Peninsula. Generally these areas are conditioned by their environmental limits such as shallow soils, seasonal and intraannual rainfall variability, which determine the availability of water for plants. The main objective of the present work is the study of soil water dynamics in dehesas, explaining the effect of different vegetation covers and soil characteristics. Soil moisture is determined in 15 stations, distributed in three farms in Extremadura, each of them composed of sensors located at various depths which register soil moisture continuously with a time resolution of 30 minutes. The stations are distributed in open areas (pasture), below the canopy of the shrub Retama sphaerocarpa and below the canopy of Quercus rotundifolia. First results indicate complex soil water dynamics with contrasting situations at sites with the same vegetation cover, and showing that various situations may be produced in the same station during a hydrological year. Furthermore, the largest variations are observed in the upper soil layer, being soil moisture variations lowest at greater depth, independently of the vegetation cover.
Keywords: bajo copa; Dehesa; humedad del suelo; pastizal; Quercus rotundifolia (voyant); retama sphaerocarpa

Prediction of near-surface soil moisture at large scale by digital terrain modeling and neural networks. - Lavado Contador, J F; Maneta, M; Schnabel, S (Environmental monitoring and assessment, 2006)
The capability of Artificial Neural Network models to forecast near-surface soil moisture at fine spatial scale resolution has been tested for a 99.5 ha watershed located in SW Spain using several easy to achieve digital models of topographic and land cover variables as inputs and a series of soil moisture measurements as training data set. The study methods were designed in order to determining the potentials of the neural network model as a tool to gain insight into soil moisture distribution factors and also in order to optimize the data sampling scheme finding the optimum size of the training data set. Results suggest the efficiency of the methods in forecasting soil moisture, as a tool to assess the optimum number of field samples, and the importance of the variables selected in explaining the final map obtained.
Keywords: Biological; Dehesa; forecasting soil moisture; humidity; Models; Neural Networks (Computer); sampling; Soil; topographic variables

Soil hydrological response under simulated rainfall in the Dehesa land system (Extremadura, SW Spain) under drought conditions - Cerdá, A; Schnabel, S (Earth Surface Processes and Landforms, 1998)
Soil hydrology was investigated in the Guadelperalón experimental watershed in order to determine the inﬂuence of land use and vegetation cover on runoff and inﬁltration within the Dehesa land system. Five soil–vegetation units were selected: (1) tree cover, (2) sheep trials, (3) shrub cover, (4) hillslope grass and (5) bottom grass. The results of the simulated rainfall experiments performed at an intensity of 53·6mm h −1 during one hour on plots of 0·25m 2 , and the water drop penetration time test indicate the importance of water repellency in the Dehesa land system under drought conditions. Low inﬁltration rates (c. 9–44mm h −1 ) were found everywhere except at shrub sites and in areas with low grazing pressure. Soil water repellency greatly reduced inﬁltration, especially beneath Quercus ilex canopies, where fast ponding and greater runoff rates were observed. The low vegetation cover as a consequence of a prolonged drought and grazing pressure, in conjunction with the soil water repellency, induces high runoff rates (15–70 per cent). In spite of this, macropore ﬂuxes were found in different locations, beneath trees, on shrub-covered surfaces, as well as at sites with a dominance of herbaceous cover. Discontinuity of the runoff ﬂuxes due to variations in hydrophobicity causes preferential ﬂows and as a consequence deeper inﬁltration, especially where macropores are developed
Keywords: Dehesa; Drought; hydrophobicity; rainfall simulation; soil hydrology

ESCORRENT~ A SUPERFICIAL EN LAS VERTIENTES DE UNA CUENCA HIDROGRÁFICA EN EL ECOSISTEMA DEHESA. CUENCA DE GUADALPERAL~ N - Ceballos, Antonio; Schnabel, S (Geographicalia, 1997)
In a sinall catchrnent under tlie deliesa landuse system overland flow production on slopes is investigated. The obtained results show tliat tl-ie determination of tl-ie tlireshold value for tl-ie generation of runoff is complex. Total precipitation and rnaxim~~m intensity in 10 minutes are the principal factors that explain tl-ie production and generatioii of slope runoff
Keywords: dehesa ecosystem; overland flow; slopes

Effect of scale on surface runoff processes - Barbancho, A C; Schnabel, S; Bolinches, C (CADERNOS DO LABORATORIO XEOLOXICO DE LAXE 21, 1996)
In a small catchment under the so-called dehesa landuse system, the production of surface runoff is investigated at different scales. This includes experiments with simulated rainfall at micro-plots, event-based measurements of overland flow at 17 open plots and 1 closed plot, and discharge production of the catchment and subcatchment. The runoff coefficients of the considered scales form two groups, with low values for the catchment and sub-catchment and high values for the microplots and hillslope plots. The results show that large part of runoff produced at the slopes is infiltrated afterwards at colluvial sites and the valley floors. Furthermore, they indicate the importance of studying at various scales in order to understand the hydrological processes operating in catchments.
Keywords: ecosystem dehesa; scale; soil erosion; surface runoff